Managing Fan Relationship after a Doping Scandal - D.E. Costin; D.L. Diaconescu; G.M. Popa; L.D. Pasarin; M.C. Popescu; V.A. Sandu; L. Velez Colon (Bulletin of the Transilvania University of Braşov: Series IX Sciences of Human Kinetics)
We all have idols in sports. People who make us wonder how they managed to become the best in their field. But there are also athletes who resort to novel and forbidden methods to skip training while trying to reach the top. What is doping and why is it banned in sports? The present paper offers a brief description of the doping phenomenon, a small review of the most famous doping cases in the history of sports, the consequences of such failure and how it influences the athlete's life, and finally a short study related to this phenomenon.